Analysis of Relationship between the Body Mass Composition and Physical Activity with Body Posture in Children. (28th September 2016) - Wyszyńska, Justyna; Podgórska-Bednarz, Justyna; Drzał-Grabiec, Justyna; Rachwał, Maciej; Baran, Joanna; Czenczek-Lewandowska, Ewelina; Leszczak, Justyna; Mazur, Artur
Abstract : Introduction . Excessive body mass in turn may contribute to the development of many health disorders including disorders of musculoskeletal system, which still develops intensively at that time. Aim . The aim of this study was to assess the relationship between children's body mass composition and body posture. The relationship between physical activity level of children and the parameters characterizing their posture was also evaluated. Material and Methods . 120 school age children between 11 and 13 years were enrolled in the study, including 61 girls and 59 boys. Each study participant had the posture evaluated with the photogrammetric method using the projection moiré phenomenon. Moreover, body mass composition and the level of physical activity were evaluated. Results . Children with the lowest content of muscle tissue showed the highest difference in the height of the inferior angles of the scapulas in the coronal plane. Children with excessive body fat had less slope of the thoracic-lumbar spine, greater difference in the depth of the inferior angles of the scapula, and greater angle of the shoulder line. The individuals with higher level of physical activity have a smaller angle of body inclination. Conclusion . The content of muscle tissue, adipose tissue, and physical activity level determines the variability of the parameter characterizing the body posture.